Formation of a doctrinal approach to public danger as a sign of crimes and administrative offenses - A. N. Alexandrov; O. A. Dizer; T. A. Nedostypenko (Правоприменение)
The purpose of the scientific article is to, based on an analysis of the concept and essence of public danger, offer scientifically based conclusions related to the understanding of whether acts should be differentiated on the grounds of “nuisance” and “danger” into administrative offenses and crimes. The achievement of the formulated goal was made possible by solving the following scientific problems: defining the concept and essence of the social danger of an act; disclosure of the content of concepts of the nature and degree of social danger of an act, clarification of their criminal legal and social functions; clarification of the influence of public danger on the criminalization of an act and the categorization of crimes.The methodological basis was the universal principles of scientific knowledge: objectivity, the relationship of phenomena and their characteristics, the unity of theory and practice. In solving the identified problems, the work also used other general scientific and special scientific methods of cognition, successfully tested by legal doctrine, including analysis and synthesis, deduction and induction.This article analyzes its concept as distinguishing an administrative offense from a crime. The essence and criteria for forming the degree of public danger are determined. Conditions are established that influence the formation of this characteristic for certain types of administrative offenses. The relationship between social danger and its degree in case of recidivism, preparation or attempted crime, and statute of limitations is analyzed.